Effects of Oil Contamination on the Geotechnical Properties of Clayey Soil - Meer Shafiul Azam; Zhong Xiao; MD Rezars Mia; MD Mafizur Rahman; Tahir Zaman (Journal of ICT, Design, Engineering and Technological Science, 2022)
The leakage of oil products which results in making the soil pollute or impure and alter its physical and mechanical properties due to the presence of hydrocarbons in it. Those hydrocarbons which cannot be passed into soil through the pores and become congest on top of the land. Hence it is necessary to indicate and know the geotechnical properties of the contaminated soil. Recently the modern technique is an encompassing laboratorial system intends to encourage and improve the high level of determining the effects of Oil contaminants on the geotechnical properties of the soil. In this way, the laboratory indications containing the fundamental properties like Atterberg limitations, direct shear, sieve analysis and unconfined compression has been taken from the contaminated soil. The contaminated samples were taken from two different areas of each site containing surface and 1m deep samples which shows the different substantial kinds of variances in the soil consequences after contamination occur in it.